The Role of The Teacher in Instruding Character Values in Autistic Students - Sole, Adriana Indra Santi (Jurnal Pendidikan Agama Kristen (JUPAK), 2023)
The purpose of this research is to find out the teacher's role in instilling character values in the Nunumeu Soe State Special School. The approach used in this research is a qualitative approach with descriptive methods. The results obtained in this study are: The teachers at the Soe Special School have carried out their roles well as role models, inspirations, motivators, dynamists and evaluators in instilling character values in autistic children.